PROGRAM UP-GRADE SKILL SERVICE SEPEDA MOTOR BAGI MEKANIK BENGKEL PEMULA DI JORONG KOTO MALINTANG - Erzeddin Alwi; Nuzul Hidayat; Wanda Afnison; Dori Yuvenda (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
The development of automotive technology is increasing rapidly along with the high level of competition among producers. According to data compiled by the Association of Indonesian Motorcycle Industry (AISI) in 2015-2016 there was an increase in the number of motorcycle sales of about 4.6% or an increase of 5.8 million units for. The high level of sales and technological developments leaving the problem for the automotive business itself. One of the problems that often happens is the slow absorption of technological progress to the hands of users. Motorcycle service workshops and bottom-line businesspeople are very vulnerable to the impact of this technology transfer process. This situation indirectly affects the sluggish economic movements among the bottom because they lack access (training and access to the latest sources of technology references). This situation should be a special concern for the top of the automotive business activists and also practitioners / academics related to the rapid development of technology produced can give impacts of rapid economic growth also for lower-level business people.The Up Grade skill program of motorcycle service involves a partner group (workshop) consisting of 6 people mechanics who are still in the beginner category. The training materials provided are tune up, conventional motorcycle overhaul (carburetor) and tune up injection motorcycle. Training is held for 2 full days (equivalent to 20 hours) with competency test process on the last day of the program. From the training activities can be seen the improvement of mechanical competence obtained from the pre-test at the beginning of the training and post test at the end of the activity.Through the program of Community Service of Regular Science and Technology is expected proposers can play its role as an academic in helping accelerate the process of technology transfer, especially for lower-level business people who do have limited access to technology. After the end of this program is expected to increase the mechanical skills as well as the increased service quality and competitiveness of partner workshops.